Continuous Monitoring of a Tumbling Mill - Kent T. Tano; Bertil I. Pålsson; Sture V. Persson (International Mineral Processing Congress, 2003)
"Grinding is one of the most energy consuming unit operations and is also a very inefficient and costly process. Therefore, it is of great importance to run the grinding process as efficiently as possible. The most common way today to control grinding processes is by measuring the power draw of the mill and try to keep it at a maximum level. However, some studies (Kawatra, 1989, Koivistoinen, 1989, Moys, 1989) have shown that this measurement doesn.t reflect everything that takes place inside a mill. Among other parameters like slurry rheology, temperature and charge behaviour, the volumetric filling of a grinding mill seems to have a large influence on the grinding efficiency (Herbst, 1988, Koivistoinen, 1992, Vermeulen, 1988). A problem in attempting to measure those parameters has been to get a sensor that is both robust and sensitive enough for continuous on-line measurement.This paper presents a method for the measurement of the apparent filling level in a pilot ball mill equipped with the Metso Continuous Charge Measurement system (CCM). In this technique a strain gauge sensor is mounted on a flat steel spring which is fitted into a recess underneath a lifter bar. In addition, a conductivity probe, the Boliden Grinding Measurement System (GMS), is mounted in another lifter bar with the purpose of comparing the two measurements. To visualise the behaviour of the charge a DEM modelling technique is used.The results indicate that the system is capable of following the normal variation that occurs in the mill. The signal also very well reflect changes in operating variables such as ball charge level, pulp density and rotational speed. By studying the nature and different features of the signal one can get a better understanding of milling circuit dynamics. Another feature of the technique is the possibility for an operator to continuously follow the grinding process and thereby run the process under optimal conditions."